ANALISIS LOG LINEAR TERHADAP FAKTOR-FAKTOR RESIKO CARCINOMA SERVIX UTERI DI RS BETHESDA YOGYAKARTA TAHUN 2002-2004 - Edy Wibowo; Ade Yayu Ratna Inten (Jurnal Ilmiah Farmasi, 2005)
ABSTRACTThis research was done at Yogyakarta Bethesda hospital Jend. Sudirman, as a mean to knowthe association among risk factors at disease of Carcinoma servix uteri. This study used secondarydata from medical records and conducted with retrospektif method. The subjects in this researchwere patient of Carcinoma servix uteri at Bethesda hospital from 2002-2004. From the medicalrecords, researcher used three variables, they were age of patient, children amount and age whenthe patient first married. Statistical analysis that used was Log Linear analysis with BackwardElimination method with level of signifikansi equal to 0.15. From the analysis result can beconcluded that there were interaction between children amount, age of patient and age when thepatient first married to the prevalence of carcinoma servix uteri. The woman with children amountmore than 5 people, above age 50 year and also age of first married less than 20 year will have thehighest possibility to have carcinoma servix uteri.Key words : carcinoma servix uteri, risk factor and log linear analysis.